Analysis of Errors in Using Words and Punctuation on Housing Advertising Banners in Jatiasih District, Bekasi City and Their Implications for Indonesian Language Learning - Awwalina Risma Octaviani; Jatut Yoga Prameswari; Siti Muharomah (DIROSAT: Journal of Education, Social Sciences & Humanities, 2023)
This study aims to analyze the errors in the use of words and punctuation on housing advertisement banners. The purpose of this study is to find out and describe the forms of word errors and punctuation on housing advertisement banners. This type of research is qualitative research which describes the data using a series of sentences. The method in this study is a qualitative method based on the philosophy of postpositivism, used to research on natural object conditions, (as opposed to experiments) where the researcher is the key instrument. Data collection techniques are carried out triangulation (combined), data analysis is inductive/qualitative, and the results of qualitative research emphasize eating more than generalization. The research technique used is to describe and understand the existence of errors in the use of words and punctuation on housing advertisement banners. Based on the results of the study, it was found that the form of errors in the use of the word aspects of accuracy, and aspects of conformity was found. Errors in the use of punctuation consisting of: (1) errors in the use of punctuation marks (.), (2) errors in the use of punctuation marks (,), (3) errors in the use of punctuation marks (-), (4) errors in the use of punctuation marks punctuation (-), (5) errors in the use of exclamation marks (!), (6) errors in the use of quotation marks (“…”), (7) errors in the use of single quotation marks ('...') , and (8) errors in using slash punctuation (/). In writing one must understand the rules of writing, one of which is the use of standard words and the use of PUEBI, so that writing complies with good and correct rules in the use of capital letters, punctuation marks , and word writing